(untitled) (International Journal of Physiotherapy, 2016)
Background: Hamstring injury is a common problem in many sports, especially those involving acceleration and maximal sprints. Hamstring strains are both common and painful. During sprinting the hip flexor and knee extensor torques are frequently produced and is opposed by the hamstring muscles, hence there are numerous studies done on the muscle strength training to prevent the hamstring strain injury as it is statistically stated as the highest rate involved injury in the contact sport. This study has been focused to evaluate the effectiveness of concentric and eccentric exercises in improving hamstring muscle strength and power among futsal players. Method: Thirty recreational futsal players were recruited for the study and were randomly divided into two groups. Each group received either hamstring curl exercise (concentric) or Nordic hamstring exercise (eccentric) twice a week for 4 weeks. The manual muscle test (MMT) and 40-yard dash test was used to evaluate the muscle strength and power respectively by comparing the pretest and posttest values for both groups. Results: Wilcoxon signed rank test showed that there is no statistically significant difference between pre and post test values of MMT (Concentric (right side, z=.317; left side, z=.157), Eccentric (right side, z=.157; left side, z=.317)) in both groups. Based on paired ’t’ test there is a significant difference between the pre and post test on improving muscle power [Concentric group, P=.020; Eccentric Group, P=.000]. Mann–Whitney U test and unpaired ’t’ test showed that there is no significant difference between both groups of MMT (z=.775) and 40-yard dash test (P=.707) respectively. Conclusion: The concentric strength training and eccentric strength training have a similar effect in improving hamstring muscle power in futsal players.